1985
DOI: 10.1007/bf00048095
|View full text |Cite
|
Sign up to set email alerts
|

Studies on rat mammary adenocarcinomas: a model for metastasis

Abstract: Studies carried out by the authors on the rat mammary adenocarcinoma cell lines MAT 13762 and DMBA-8 are summarized. A series of variants and somatic cell hybrids have been prepared and partially characterized in terms of phenotypic properties which may correlate with metastatic potential. These include measurement of in vitro migration, lectin binding properties, expression of procoagulant activity and shedding of cell surface components. Particular emphasis has been placed on the production of enzymically-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…In addition it may facilitate the aggregation of cancer and blood ceils (usually platelets) which promote the arrest of these aggregates in capillaries and induce the initial phase of their adhesion to the capillary endothelium [6]. Recent studies demonstrated strong positive correlations between PCA and lung tumor colonization [12,20]. Accordingly, inactivation of PCA by heparin proved to be an excellent adjuvant to immunostimulating therapy [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition it may facilitate the aggregation of cancer and blood ceils (usually platelets) which promote the arrest of these aggregates in capillaries and induce the initial phase of their adhesion to the capillary endothelium [6]. Recent studies demonstrated strong positive correlations between PCA and lung tumor colonization [12,20]. Accordingly, inactivation of PCA by heparin proved to be an excellent adjuvant to immunostimulating therapy [5].…”
Section: Discussionmentioning
confidence: 99%
“…Human leucocyte preparation and activation as well as measurement of humoral IgM response (direct plaque forming method) were carried out as previously described [20].…”
Section: Methodsmentioning
confidence: 99%
“…Rat mammary carcinoma cell lines The derivation and characteristics of cell lines derived from the chemically-induced rat mammary adenocarcinomas DMBA-8 and MAT 13762, have previously been described in some detail (Ramshaw & Badenoch-Jones, 1985;Ramshaw et al, 1986). The original parent cell line adapted from the DMBA-8 tumour , is capable of forming tumours but does not metastasise in syngeneic Fischer 344 rats (Ramshaw & Badenoch-Jones, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…A minimal in vivo selection of DMBA-8-derived clones, resulted in cell lines which were completely non-metastatic (NM4) or highly metastatic (metastatic ascites, MA; metastatic clone 2, MC2) when injected sub-cutaneously or via tail vein into host animals (originally described in Ramshaw & Badenoch-Jones, 1985;Ramshaw et al, 1986;Dear et al, 1989). The MAT 13762 parent cell line, by contrast, was itself highly metastatic in syngeneic Fischer 344 rats (originally described in Ramshaw & Badenoch-Jones, 1985). A MAT 13762 6-thioguanine-resistant variant (J-clone), however, maintained some tumour-forming potential but was found to be consistently incapable of metastasising in syngeneic host rats (Ramshaw et al, 1982).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation